Fertilization Alters Indicator Species Serving as Bioindicators for Evaluating Agricultural Practices Related to Maize Grain Yield - Guoqiang Li; Jiaqing Liu; Wenya Zhang; Jvshui Hu; Peng Shi; Gehong Wei (Microorganisms, 2025)
Diversified agricultural practices reconfigure agroecosystem services by modifying fertilization, tillage intensities, and cropping patterns, altering soil properties and microbial assemblages. However, microbial communities, as critical bioindicators of soil health and productivity, respond to agricultural disturbances, and the effects of multiple practices on productivity-associated indicator species require further validation. Using 16S and ITS amplicon sequencing, this study employed a field experiment to investigate the effects of agricultural practices on soil properties, maize productivity, and microbial communities under two fertilization treatments. Within each treatment, we assessed correlations between indicator species associated with cropping–tillage practices and soil productivity. Results showed that fertilization significantly altered soil properties, increased maize grain yield by 23.9%, and reshaped bacterial and fungal community structures, increasing bacterial richness by 23% but reducing fungal richness and Shannon index by 15% and 20%, respectively. Furthermore, cropping–tillage practices significantly affected microbial communities and grain yields in both fertilized and unfertilized treatments despite a slight influence on soil properties. Distinct sets of bacterial and fungal indicator species were identified for each fertilization treatment: unfertilized soils harbored 21 dominant bacterial indicator species (e.g., Bacillus, Rhizobium, Streptomyces) and 8 fungal indicators (e.g., Cryptococcus, Gibberella, Tetracladium); fertilized soils contained 24 dominant bacterial indicators (e.g., Fusobacterium, Clostridium, Lactobacillus) and 6 fungal indicators (e.g., Gibberella, Cladosporium, Mortierella). Notably, abundances of specific indicator genera (e.g., bacteria: Bacteroides, Gemmatirosa, Iamia, Lysobacter, Prevotella, Staphylococcus, Sutterella; fungi: Glomus, Fusicolla in unfertilized soil; bacteria: Dinghuibacter, Haliangium, Kribbella, Rhodomicrobium, Terrimonas; fungi: Pulvinula in fertilized soil) correlated positively with grain yields. These findings demonstrate that fertilization reshapes the composition of microbial indicator species significantly associated with maize productivity. Tailored microbial indicator assemblages specific to distinct fertilization strategies are therefore essential for evaluating crop productivity and assessing agricultural practice impacts. Consequently, monitoring these indicator species enables rapid assessment of soil fertility changes, offering guidance for fertilization management.